MANAJEMEN PEMERINTAHAN DAERAH DALAM GADUHAN TERNAK DI KABUPATEN ROKAN HULU TAHUN 2012-2016 (Studi : Gaduhan Sapi di Kabupaten Rokan Hulu) - Rama Ady Yatma As; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Gaduhan cattle is giving lending aid cattle to public repayment of cattle. The mechanism of assistance through gaduhan cattle that is the community joining the farmers only have to make proposals the seed assistance cattle to the office of fisheries and farms Rokan Hulu Regency. Farmers groups beneficiaries it will then known as recipients gaduhan. Recipients gaduhan would have a duty to return gaduhan cattle received earlier in the period 3 years seedlings cattle also, the son of gaduhan cattle formerly received earlier.. Gaduhan these animals more in prioritizing to cattle because the development of a cow in Rokan Hulu more effective and strategic so this way the goverments try to accelerate the recipient and equity cattle calf to every districts in the Rokan Hulu Regency and to achieve the target swasembada beef and program a million beef in Rokan Hulu Regency.Keywords: Management, Gaduhan,Target